Ethanol lock therapy (E-Lock) in the prevention of catheter-related bloodstream infections (CR-BSI) after major heart surgery (MHS): a randomized clinical trial. - María Jesús Pérez-Granda; José María Barrio; Patricia Muñoz; Javier Hortal; Cristina Rincón; Pablo Martin Rabadán; Maria Sagrario Pernia; Emilio Bouza (PLoS ONE, 2014)
Background Lock-therapy with antimicrobials has been used for the treatment and prevention of catheter-related bloodstream infections (CR-BSI). Experiences with Ethanol-Locks (E-locks) have included therapeutic interventions with variable results. Patients undergoing Major Heart Surgery (MHS) are a high-risk population for CR-BSI.The aim of this study was to assess the efficacy and tolerance to E-Locks in the prevention of CR-BSI of patients undergoing MHS. Methods and findings This is an academic, prospective, randomized, non-blinded and controlled clinical trial assessing the incidence of CR-BSI of patients with E-locks (E-lock) and the tolerance to the procedure in comparison with patients receiving conventional catheter-care (CCC). Patients undergoing MHS with intravascular catheters for more than 48 hours were randomly assigned into treatment or control group by a computer-generated list of randomly assigned numbers. In the treatment group, all their catheter lumens were locked with an ethanol solution at 70% for two hours, every three days (E-Locks). The control group received conventional catheter-care (CCC). Overall, 200 patients with 323 catheters were included in the study, which was stopped after 10 months due to adverse events. Of them, 179 catheters (113 patients) had E-Locks and 144 catheters (87 patients) were CCC. Euroscore Surgical Risk in both groups was 4.04 vs 4.07 p = 0.94 respectively. The results for the E-Locks and CCC were as follows: Incidence of CR-BSI/1000 days of exposure 2.1 vs 5.2 (p = 0.33), catheter tip colonization 14 (7.8%) vs 6 (4.2%) patients (p = 0.17), median length of hospital stay, 15 vs 16 days (p = 0.77). Seven patients (6.19%), all in the ethanol branch, had to discontinue the trial due to intolerance or adverse events. Conclusions We do not recommend prophylaxis of CR-BSI with ethanol-lock on a routine basis in patients undergoing Major Heart Surgery. Trial registration Clinical Trials.gov NCT01229592.